1982
DOI: 10.2503/jjshs.50.468
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Low Temperature-induced Malformation of Tomato Fruit by Plant Growth Regulators

Abstract: Low temperature-induced fruit malformation in tomato was studied from plant hormonal view point. Treatment of TIBA (2, 3, 5-triiodobenzoic acid) and NAP (sodium N-1-naphthylphthalamic acid), auxin-transport inhibitors, increased locule numbers and induced severe malformation including catfaced and strawberry fruits with ovary splits, and oblate and fasciated fruits. Bendroquinone (2-benzimidoyl-3hydroxyl-1, 4-napthoquinone), which is considered to have the similar action mechanism to TIBA and NPA, also showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1984
1984
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…1) are in strong contrast to the results of Saito and Ito (1971), who reported that 6 days at 17/8C induced doubling of the average number of locules per fruit in their material. Multilocular genotypes, with eight to 16 locules, like those used by Saito and Ito (1971), apparently were more sensitive to low temperature-induced locule proliferation than genotypes with only a few (three to seven) locules per fruit (Asahira et al, 1982;Rylski, 1979;Sawhney and Polowick, 1985). In the present experiment, increases in average BSI did not coincide with increases in the average number of locules in the same fruit (Fig.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…1) are in strong contrast to the results of Saito and Ito (1971), who reported that 6 days at 17/8C induced doubling of the average number of locules per fruit in their material. Multilocular genotypes, with eight to 16 locules, like those used by Saito and Ito (1971), apparently were more sensitive to low temperature-induced locule proliferation than genotypes with only a few (three to seven) locules per fruit (Asahira et al, 1982;Rylski, 1979;Sawhney and Polowick, 1985). In the present experiment, increases in average BSI did not coincide with increases in the average number of locules in the same fruit (Fig.…”
Section: Discussionsupporting
confidence: 54%
“…The occurrence of cat facing has been associated with prolonged cool weather early in the growing season (Knavel and Mohr, 1969;Sherman and Allen, 1981;Stevenson and Heimann, 1981). In addition to catfacing, long-term 5 weeks) low-temperature treatments, applied between cotyledon expansion and anthesis, caused fascination (Sawhney and Polowick, 1985), triangular fruits (Hosoki et al, 1985), navel-like scars, puffiness, seedless fruits (Rylski, 1979), and "strawberry" fruits with split ovary (Asahira et al, 1982). Most of these malformations were attributed to an increase in the number of locules (Asahira et al, 1982;Kaneme and Itagi, 1966;Sawhney and Polowick, 1985).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The seedlings at 2-true leaf stage were cultured in Mie University nutrient solution of half strength (1) in which only nitrogen was modified to double amount or one fif tyth amount ; NH4C1 and NaNO3, or NaHPO4.12 H20 and CaC12.2 H2O were supplemented respectively to maintain a balance with the other elements (P and Ca).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, seedless fruits produced under low temperatures frequently suffer some type of malformation (Asahira, Hosoki and Shinya, 1982) as do fruit induced by growth regulators (Osborne and Went, 1953). Various fruit abnormalities often accompany parthenocarpic fruit production.…”
Section: Comparative Performance Of Seeded Vs Parthenocarpic Tomato Fmentioning
confidence: 99%